A community pharmacy-based cardiovascular risk screening service implemented in Iran - Jahangard-Rafsanjani Z; Hakimzadeh N; Sarayani A; Najafi S; Heidari K; Javadi MR; Hadjibabaie M; Gholami K. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Cardiovascular disease is a major health concern around the world. Objective: To assess the outcomes and feasibility of a pharmacy-based cardiovascular screening in an urban referral community pharmacy in Iran. Methods: A cross sectional study was conducted in a referral community pharmacy. Subjects aged between 30-75 years without previous diagnose of cardiovascular disease or diabetes were screened. Measurement of all major cardiovascular risk factors, exercise habits, medical conditions, medications, and family history were investigated. Framingham risk score was calculated and high risk individuals were given a clinical summary sheet signed by a clinical pharmacist and were encouraged to follow up with their physician. Subjects were contacted one month after the recruitment period and their adherence to the follow up recommendation was recorded. Results: Data from 287 participants were analyzed and 146 were referred due to at least one abnormal laboratory test. The results showed 26 patients with cardiovascular disease risk greater than 20%, 32 high systolic blood pressure, 22 high diastolic blood pressures, 50 high total cholesterol levels, 108 low HDL-C levels, and 22 abnormal blood glucose levels. Approximately half of the individuals who received a follow up recommendation had made an appointment with their physician. Overall, 15.9% of the individuals received medications and 15.9% received appropriate advice for risk factor modification. Moreover, 7.5% were under evaluation by a physician. Conclusion: A screening program in a community pharmacy has the potential to identify patients with elevated cardiovascular risk factor. A plan for increased patient adherence to follow up recommendations is required.